USE OF FROZEN BAIT BOOSTERS ON 2-DECKS HOOPNET TRAP FISHING OPERATION WITH COLONY SYSTEM AT PALABUHANRATU BAY - Zulkarnain; Wazir Mawardi; Furqan; Mustaruddin; Hafiyyan Naufal (Jurnal Penelitian Perikanan Laut (Albacore), 2026)
Previous research on comparing 2-decks hoopnet traps compared to traditional hoopnet traps with frozen bait boosters demonstrated an increase in crustacean catch yields. The present study represents a further development of that earlier work. This research was conducted to determine differences in catch composition and to assess the catch productivity and fishing effectiveness of 2-decks hoopnet traps with frozen bait boosters (treatment) compared to 2-decks hoopnet traps without frozen bait boosters (control). Data analysis methods employed included descriptive analysis, normality testing, and productivity assessment. Catch composition for the treatment and control 2-decks hoopnet traps, respectively, was as follows: 61.1% and 38.9% for blue swimmer crab (Portunus pelagicus), 55.7% and 44.3% for batik crab, and 60% and 40% for ornate rock lobster. Operation of the treatment 2-decks hoopnet traps under a colony system yielded a greater influence on and a higher number of crustacean catches compared to the control across all trips throughout the study period. Overall catch from the treatment 2-decks hoopnet traps was higher than that of the control. The fishing effectiveness of the treatment 2-decks hoopnet traps relative to the control exceeded 40% in both weight (kg) and number (individuals). Key words: colony system operation, crustaceans, 2-decks hoopnet trap, frozen bait booster